This truck has got to be special - Rana, Anjum; Kulavoor, Sameer; Nawaz, Hakeem; Khan, Amer (India Tara Books, 2016)
Gul -- who drives along the mountain roads of the Karakoram and the Hindu Kush -- has finally acquired his own vehicle and wants it painted beautifully. As Zarrar gets to work, Gul waits in the yard, thinking about his many journeys, the splendour of the hills and the intricacies of truck art -- until everything is at last ready and it's time to be off on the road again. This book celebrates the energy and joy of Pakistani truck art as well as the artists whose skill and labour breathe life into it.
Junior primary school age.
Keywords: Art, Pakistani -- Juvenile fiction; Truck drivers -- Pakistan -- Juvenile fiction; Pakistan -- Juvenile fiction